E-Government, Managerial Staff Preparation and Cognitive Society - Ihar Ivanavich Hancharonak (Управленческое консультирование, 2018)
In the context of E-Government and cognitive society development the necessity of managerial staff with new professional competencies preparation within innovative educational programs is actualized.